Peran Guru Pendidikan Agama Kristen dalam Membangun Konsep Diri Positif Peserta Didik - Riskha, Oktavia; Wicaksono, Arif (Sekolah Tinggi Agama Kristen Luwuk Banggai, 2024)
A positive self-concept that arises from within a person begins with one's beliefs and positive mindset about their abilities and potential. A negative self-concept is directed at how a person feels ashamed of their physical differences, lacks self-confidence, avoids asking teachers/educators for help when they don't understand the material, refrains from expressing opinions, and avoids making friends. The purpose of this discussion is to improve and change an individual's irrational attitudes, perceptions, beliefs, and views into rational ones, thereby enabling personal development and achieving optimal self-realization. The type of research conducted in this paper is qualitative. With the role of educators in rebuilding a positive self-concept for students, there can be a transformation in students. They will no longer be ashamed of their physical appearance, and they will be willing to accept their shortcomings and strive to optimize their potential.